Ревизор: комедия : в 5 действиях / Н. В. Гоголь - Гоголь Николай Васильевич (Логосвос, 2019)
Экземпляры: БС (20190821) / Инвентарный номер: РТШ54788 / Цена: / Сис.шифр: Р1 / Авт.знак: Г 58 / ГРНТИ: 17.82.20 / ББК: 84(2)